Impact of exchange rate depreciation on the balance of payments: Empirical evidence from Nigeria - Martins Iyoboyi; Olarinde Muftau (Cogent Economics & Finance, 2014)
The paper investigates the impact of exchange rate depreciation on the balance of payments (BOP) in Nigeria over the period 1961 - 2012. The analysis is based on a multivariate vector error correction framework. A long-term equilibrium relationship was found between BOP, exchange rate and other associated variables. The empirical results are in favour of bidirectional causality between BOP and other variables employed. Results of the generalized impulse response functions suggest that one standard deviation innovation on exchange rate reduces positive BOP in the medium and long term, while results of the variance decomposition indicate that a significant variation in Nigeria's BOP is not due to changes in exchange rate movements. The policy implication is that exchange rate depreciation which has been preponderant in Nigeria since the mid-1980s has not been very useful in promoting the country's positive BOP. It is recommended that growth in the real sector should be improved to enhance exports, create employment, curb inflation and reduce poverty, while cutting non-productive imports, attracting foreign private investment and implementing well coordinated macroeconomic policies that impact inflation positively and stimulate exchange rate stability.
Keywords: C32; E44; E52; E63; 330; balance of payments; cointegration; depreciation; exchange rate; generalized impulse response functions; vector error correction model